TJS 2016
DOI: 10.15547/tjs.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of crystal meth in parallel with oxidative stress impaired spatial memory in prefrontal cortex of mail rats

Abstract: Methamphetamine has neurotoxic effects on serotonergic, dopaminergic systems. These systems are responsible for learning and memory functions. Also oxidative stress is known to play a prominent role in the neurocognitive deficit, so the aim of present study is evaluates the effect of crystal meth on spatial learning and memory in parallel with oxidative stress parameters. 28 Male mice were randomly divided into 4 groups, including (I: sham, saline), (II: crystal meth 5 mg/kg), (III: crystal meth 10mg/kg); and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“… 82 It has been shown that the prefrontal cortex and hippocampus are primarily involved in the modulation of spatial learning and memory and oxidative stress in these key brain areas results in spatial memory impairment. 83 Vitamin C, a natural antioxidant, has been documented to facilitate hippocampal antioxidant enzyme activity thereby improving cognitive function. 84 We found that 6-MOF treatment curtailed ethanol repressed frontal cortical vitamin C levels and this may have contributed to improved Morris water maze performance.…”
Section: Discussionmentioning
confidence: 99%
“… 82 It has been shown that the prefrontal cortex and hippocampus are primarily involved in the modulation of spatial learning and memory and oxidative stress in these key brain areas results in spatial memory impairment. 83 Vitamin C, a natural antioxidant, has been documented to facilitate hippocampal antioxidant enzyme activity thereby improving cognitive function. 84 We found that 6-MOF treatment curtailed ethanol repressed frontal cortical vitamin C levels and this may have contributed to improved Morris water maze performance.…”
Section: Discussionmentioning
confidence: 99%